SYNTAX residual in long-term outcomes prognosis of endovascular revascularization in myocardial infarction with ST elevation and multivessel disease - R. S. Tarasov; V. I. Ganyukov; K. M. Vakkosov; O. L. Barbarash; L. S. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To study prognostic significance of coronary atherosclerosisseverity (residual SYNTAX) after primary percutaneous intervention (PCI) in myocardial infarction patients with STE (STEMI) and multivessel coronary lesion, in long term period.Material and methods. Totally, 317 STEMI patients included, having multivessel coronary atherosclerosis, underwent primary PCI. Patients were excluded if having hemodynamically significant left coronary stem stenosis (≥50%), and with signs of cardiogenic shock or pulmonary edema. Patients were selected to 2 groups depending on the residual lesion after primary PCI, by SYNTAX: ≤8 points (n=243) and ≥9 points (n=74). Mean follow-up was 36,7±24,3 months. The adverse cardiovascular events were taken: death, myocardial infarction (MI), second revascularization of the target and non-target vessel, as the cases of stent thrombosis.Results. Patients with the significant after primary PCI residual coronary atherosclerosis, comparing to those with mild residual SYNTAX were older — 63,1±10,6 y. vs 58,8±9,9 y., resp. (р=0,001), females predominated — 55,9% vs 31,3%, resp. (р=0,03), more significant was part of multivessel disease — 37,8% vs 24,3%, resp. (р=0,03), three vessel lesion predominated — 83,8% vs 49% (0,0001) and less common performing of the strategy of primary PCI — 9,5% vs 32,9%, resp. (р=0,0001). In long term follow-up (36,7±24,3 months.) among those with SYNTAX ≥9 comparing to those SYNTAX ≤8 pts. there was worse prognosis, that represented as higher mortality from all causes — 16,2% vs 5,3%, resp. (р=0,005), odds ratio (OR) 3,4 (1,5-7,9; 95% CI), (р=0,004); second MI — 16,2% vs 6,6%, resp. (р=0,02), OR 2,7 (1,2-6,1; 95% CI), (р=0,01), second non-target revascularization — 18,9% vs 8,2%, resp. (р=0,02), OR 2,6 (1,2-5,5; 95% CI), (р=0,01). Conclusion. Value of residual coronary lesion by SYNTAX ≥9 showed higher prognostic significance, seriously raising the probability of most adverse cardiovascular events. Therefore, STEMI patients with multivessel disease and residual SYNTAX ≥9 pts. after primary PCI should undergo complete myocardial revascularization that can be done via broader application of the strategy of multivascular stenting under primary PCI, and staged PCI within optimal time frame (in-hospital period).